Dramaturgy of "Hamlet"(s) in Czech Theatre between 2000 and 2023 - Drozd, David (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The paper focuses on five Czech productions of Hamlet that attracted the most critical and public attention between 2000 and 2023. Namely, the productions directed by Miroslav Krobot (2006), Jan Mikulášek (2009), Daniela Špinar (2013), Michal Dočekal (2021) and finally the most recent version by Jakub Čermák (2022). All five performances could be seen as contemporary reinterpretations of a classical text using a (post-)modern stylistic approach, as examples of post-millennium Hamlets. The paper discusses dramaturgical choices (such as the conceptualisation of the ghost, the mousetrap scene, or the character of Fortinbras) in order to identify and analyse possibilities for interpreting Hamlet as a political drama in the context of Czech performance tradition and the current political situation. The results show that performances generally present variations of Hamlet as a family drama, foregrounding different issues of memory and body, while the political reading is obsolete.